2022
DOI: 10.3390/ijms24010681
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Absorptive Microsampling in Therapeutic Drug Monitoring of Immunosuppressive Drugs—From Sampling and Analytical Issues to Clinical Application

Abstract: Miniaturisation and simplification are novel approaches in clinical bioanalysis, especially in therapeutic drug monitoring (TDM). These contemporary trends are related to the sampling, pre-treatment, and analysis of biological fluids. Currently, dried blood spot (DBS), one of the most popular microsampling techniques, is feasible and inexpensive. However, obtaining reliable results with sample homogeneity and volume variability is difficult. Volumetric Absorptive Microsampling (VAMS) has recently enabled the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In addition, the introduction of the VAMS technique in routine TDM enables to increase in the adherence of the patients to the therapy, as it allows home sampling without the assistance of trained personnel. Dried Mitra sticks can be delivered to the laboratory, packed in envelopes, and sent via standard postal services [26]. Moreover, several authors using the questionnaire forms confirmed that VAMS home sampling is preferred over traditional blood sampling in the case of routine monitoring [27,28].…”
Section: Volumetric Absorptive Microsamplingmentioning
confidence: 99%
“…In addition, the introduction of the VAMS technique in routine TDM enables to increase in the adherence of the patients to the therapy, as it allows home sampling without the assistance of trained personnel. Dried Mitra sticks can be delivered to the laboratory, packed in envelopes, and sent via standard postal services [26]. Moreover, several authors using the questionnaire forms confirmed that VAMS home sampling is preferred over traditional blood sampling in the case of routine monitoring [27,28].…”
Section: Volumetric Absorptive Microsamplingmentioning
confidence: 99%
“…Microsampling offers several practical advantages over traditional samples, such as minimal invasiveness for patients and simplified logistical requirements. Although equivalence with or without correction factors has been demonstrated in many cases [5][6][7][8][9], it is necessary to validate drug-specific reference/target ranges for each microsampling device. In fact, because of possible differences in the drug concentrations among alternative matrices (capillary blood, urine, breast milk, saliva) [10] and possible interactions of analytes with filtration or adsorption materials, which must be evaluated during method development [11], the reference/target ranges established for TDM in plasma cannot be transferred directly to microsamples [12].…”
Section: Introductionmentioning
confidence: 99%
“…In our recently published review study, the currently developed methods for immunosuppressants determination (including TAC) in VAMS samples were prescribed [ 11 ]. Based on that, the main advantages of the VAMS LC-MS/MS method developed in that study are: the shortest time of sampler drying (1 h) and analytical run (5 min), simple extraction solvent (water), and finally, hematocrit evaluation and clinical cross-validation.…”
Section: Introductionmentioning
confidence: 99%